2010
DOI: 10.1016/j.fertnstert.2010.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial expression of relaxin and relaxin receptor in endometriosis

Abstract: Narrative AbstractOur studies demonstrate significantly lower expression of relaxin and its receptor in ectopic endometriotic tissues than their expression in eutopic endometrium and in endometrium from normal controls. These data suggest that in normal and eutopic endometrium, relaxin may exert a protective effect against endometriosis.The etiology of endometriosis, defined as the presence of endometrial stromal and glandular tissue growing at an extrauterine site, is poorly understood. The Sampson theory (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Rxfp1 mRNA is detected in both proliferative and secretory phase endometrial samples. 52,[55][56][57] Although some studies report increased expression during the secretory phase relative to the proliferative phase, 51,52,55 others suggest constitutive expression throughout the menstrual cycle, 56,57 with considerable variation in expression among different patients. 57 In agreement with studies examining tissue expression, there was large variation in Rxfp1 mRNA expression among isolated cell cultures derived from different patients.…”
Section: Uterusmentioning
confidence: 99%
“…Rxfp1 mRNA is detected in both proliferative and secretory phase endometrial samples. 52,[55][56][57] Although some studies report increased expression during the secretory phase relative to the proliferative phase, 51,52,55 others suggest constitutive expression throughout the menstrual cycle, 56,57 with considerable variation in expression among different patients. 57 In agreement with studies examining tissue expression, there was large variation in Rxfp1 mRNA expression among isolated cell cultures derived from different patients.…”
Section: Uterusmentioning
confidence: 99%
“…Relaxin, a hormone produced by the corpus luteum in pregnancy that loosens the pelvic ligaments in preparation for childbirth, has been proposed as a specific target hormone for the ligament injury and development of arthritis as a result of attenuation of the supporting joint ligaments [45]. Relaxin is a member of the insulin superfamily, produced by the uterine endometrium in nonpregnant women [15,27] and in the prostate in men [44] and has been demonstrated in postmenopausal women [3] as well. As a potential mediator of laxity in the stabilizing ligaments of the thumb CMC joint, relaxin has been shown to be present in both males and females in a circulating form [31] and a previous study showed receptors present in the anterior oblique ligaments of women [26].…”
Section: Introductionmentioning
confidence: 99%
“…Endometriotic cysts express matrix metalloproteinases (MMP) and angiogenic factors in higher amounts with respect to eutopic endometrium, suggesting that the endometrial tissue undergoes modifications that enable its implantation in the peritoneal cavity and pelvic organs (4). Moreover, ectopic endometrium has a decreased expression of relaxin and urocortin messenger RNA (mRNA) expression, which supports a difference with eutopic tissue (5,6). Expression of estrogen and progesterone receptors is quantitatively altered in endometriotic tissue and biologically significant quantities of progesterone and estrogen are produced locally in endometriotic tissue through an abnormally active steroidogenic cascade (2).…”
mentioning
confidence: 99%